Too little, too imbalanced: Nutrient supply in smallholder oil palm fields in Indonesia - Lim, Ya Li (2023)
CONTEXT: Smallholders account for ca. 40% of oil palm area in Indonesia but average yield remains low. Despitehigher overall fertilizer use in Indonesia compared with other Southeast Asian countries, poor plant nutrition hasbeen identified as a major factor explaining yield gaps in smallholder oil palm fields and little is known about theunderlying management drivers.OBJECTIVE: To assess nutrient management in smallholder fields and identify entry points to narrow the existingyield gap via improved plant nutrition.METHODS: We assessed nutrient balances and gaps for nitrogen (N), phosphorous (P), potassium (K), andmagnesium (Mg) and inter-relationships between fertilizer use, leaf nutrient concentration, and yield, using datacollected from 977 smallholder fields in Indonesia over two years.RESULTS AND CONCLUSIONS: There was a positive relationship between yield and nutrient rates, especially forpotassium (K). Only half of the fields received fertilizer and average nutrient rates in fertilized fields represented45% (N), 83% (P), 28% (K), and 25% (Mg) of the associated removal with harvested yield. Applied fertilizer wasgenerally rich in N and P, but poor in K and Mg, leading to nutrient imbalances. Additionally, farmers did notfollow appropriate practices on fertilizer placement and splits. Improving current fertilizer supply and managementis needed to increase smallholder yields and profit.SIGNIFICANCE: Current agricultural and research programs will benefit from re-orienting efforts to improvenutrient management in oil palm as a pathway to narrow yield gaps in smallholder fields, which, in turn, requiresstrengthening extension services to fill in knowledge gaps and tune subsidy programs to facilitate farmer accessto fertilizer sources more suited to the crop.